The Effects of Israeli Policies on Palestinians' Basic Needs in the Occupied West Bank and East Jerusalem - Marta Parigi; Hamid R. Oskorouchi (Institute of Labor Economics (IZA), 2024)
This study quantitatively evaluates conclusions of NGOs, UN agencies, and the International Court of Justice denouncing the purported practices of apartheid by Israel. We gauge the impact of Israeli policies on Palestinian basic needs using a bespoke index and a novel instrumental variable (IV)-georeferenced mentions of Old Testament sites within a five-kilometre radius of each Palestinian locality. The instrument's exclusion restriction is validated by robustness checks and placebo tests (e.g., employing a placebo-IV built using New Testament-only landmarks). Our findings corroborate qualitative and legal research documenting how Israel's policies systematically undermine Palestinians' rights, potentially constituting an apartheid regime. This work could serve as evidence in prospective legal proceedings.
Keywords: D74; J71; K33; 330; Palestine; Israel; basic needs; discrimination; apartheid